Unbound hukou and rebound innovation in urban China - Chong Lu; Xingyu Qian (Humanities & Social Sciences Communications)
Abstract The Chinese authorities issued the “Guiding Opinions on Further Deepening the Reform of the Household Registration System” in 2014. This policy maintained strict controls on urban hukou in megacities, while slightly less stringent controls were applied in large cities. However, the restrictions on obtaining urban hukou were significantly relaxed in medium-sized cities and completely lifted in small cities. This study examines the causal effects and underlying mechanisms of hukou reform on urban innovation in cities of different sizes, using DID method based on a quasi-natural experiment by the 2014 hukou reform in China. The findings suggest that the hukou reform can significantly promote urban innovation, with particularly strong positive effects observed in large cities in the eastern region, small- and medium-sized cities in the central and western regions, as well as cities with favourable conditions for innovation. The primary mechanisms in which hukou reform influences urban innovation involve enhancing both the quantity and quality of urban labor force, as well as creating a better environment for innovation in cities.